Walk 8 ON MARATA STREET… - -, - (project baikal, 2011)
Russian-Asian Bank Building, Lenin Street 38The House with StalinMetropol Hotel “Little Bodies May Have Great Souls”. House on Marata Street 41“What Marvels There! A Mermaid Sitting High in a Tree, a Sprite, a Trail”. House on Marata Street 62“Sometimes There is Complexity Hiding in Simplicity”. House on Marata Street 60“West and East”. House on Marata Street 54“The Houses for Specialists” in the USSRThe First House for Specialists in IrkutskBazanov’s Foster Home